Ursodeoxycholic and chenodeoxycholic bile acids alleviate endotoxininduced acute lung injury in rats by modulating aquaporin expression and pathways associated with apoptosis and inflammation - Milivojac, Tatjana; Grabež, Milkica; Amidžić, Ljiljana; Prtina, Alma; Krivokuća, Aleksandra; Malicevic, Ugljesa; Barudžija, Maja; Matičić, Milka; Uletilović, Snežana; Mandić-Kovačević, Nebojša; Cvjetković, Tanja; Stojiljković, Miloš P.; et al. (Frontiers in Pharmacology, 2025)
IntroductionThis study aimed to investigate the anti-inflammatory, antioxidant, and anti-apoptotic properties of ursodeoxycholic (UDCA) and chenodeoxycholic (CDCA) bile acids in a rat model of endotoxin (lipopolysaccharide, LPS)-induced acute lung injury (ALI).MethodsThe study included six groups of Wistar rats exposed to different pretreatments. The control and endotoxin groups were pretreated with propylene glycol, a solvent for bile acids, while the other groups received UDCA or CDCA for 10 days. On the 10th day, an endotoxin injection was given to evaluate the impact of these pretreatments. Lung tissue sections were analyzed by immunohistochemistry, targeting the pro-inflammatory marker nuclear factor kappa B (NF-κB), the anti-apoptotic marker B-cell lymphoma 2 (BCL-2), pro-apoptotic markers BCL-2-associated X protein (BAX) and caspase 3, as well as the aquaporins 1 and 5 (AQP1 and AQP5). Oxidative stress was assessed in bronchoalveolar lavage fluid (BALF).Results and discussionThis study demonstrates that UDCA and CDCA can mitigate endotoxin-induced lung injury in rats. These effects are achieved through modulation of AQP1 and AQP5 expression, reduction of oxidative stress, regulation of apoptotic pathways (BAX, caspase 3, BCL-2), and attenuation of pro-inflammatory activity of NF-κB. Although the results indicate a significant association between the expression of these proteins and histopathological changes, the potential influence of additional factors cannot be excluded. These findings suggest that UDCA and CDCA provide lung protection by acting through complex mechanisms involving inflammatory, oxidative, and apoptotic pathways.